Trombocitopenia Inducida por Rifampicina (2018)
ABSTRACT: Rifampicin-induced thrombocytopenia is a rare but potentially fatal immune phenomenon. We report the case of an immunocompromised patient with disseminated tuberculosis who developed rifampicin-induced thrombocytopenia 12 hours after starting anti-tuberculous therapy without previous drug sensitization. The cause-effect relationship was confirmed when thrombocytopenia resolved with rifampicin suspension but later reappeared upon drug re-exposure.